2003
DOI: 10.1002/jcp.10435
|View full text |Cite
|
Sign up to set email alerts
|

ERK1/2 mediates TNF‐α‐induced matrix metalloproteinase‐9 expression in human vascular smooth muscle cells via the regulation of NF‐κB and AP‐1: Involvement of the ras dependent pathway

Abstract: The expression of matrix metalloproteinase-9 (MMP-9) has been implicated in progression of atherosclerotic lesions. The role and importance of the signaling pathway in the transcriptional regulation of MMP-9 in human aortic smooth muscle cells (HASMC) was examined. Tumor necrosis factor-alpha (TNF-alpha) stimulated the secretion of MMP-9 in HASMC, as shown by zymography and immunoblot analysis. At the transcriptional levels, TNF-alpha also stimulated the 5'-flanking 710-bp promoter activity of MMP-9. Transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
324
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 286 publications
(338 citation statements)
references
References 43 publications
13
324
0
1
Order By: Relevance
“…To date, three transcription factors (p53, NF-kB and the SP1-related retinoblastoma control proteins) appear to be responsive to the physiological radiation dose, the dose wherein cells survive or recover (Moon et al, 2004). In this study, NF-kB but not AP-1, modulated the radiation-induced MMP-9 activity in HepG2 cells on zymography.…”
Section: Discussionmentioning
confidence: 73%
“…To date, three transcription factors (p53, NF-kB and the SP1-related retinoblastoma control proteins) appear to be responsive to the physiological radiation dose, the dose wherein cells survive or recover (Moon et al, 2004). In this study, NF-kB but not AP-1, modulated the radiation-induced MMP-9 activity in HepG2 cells on zymography.…”
Section: Discussionmentioning
confidence: 73%
“…26,48 Evidence presented in this study suggests that the potential mechanism for MMP-1 induction and activation may involve the generation of ROS and TNF-␣ by infiltrated neutrophils. This notion is supported by studies 13,15,16,49 showing that TNF-␣ and ROS modulate the expression of different MMPs in VSMCs and promote the activation of MMPs secreted by VSMCs. The fact that the exposure of VSMC to neutrophils or neutrophil products, such as TNF-␣ and ROS, resulted in a similar extracellular matrix gene expression pattern as that observed in blood vessels from preeclamptic women provides further evidence for the in vivo role of neutrophils in the vascular remodeling process occurring during preeclampsia.…”
Section: Discussionmentioning
confidence: 81%
“…9,10 Neutrophils produce inflammatory mediators, such as reactive oxygen species (ROS) and tumor necrosis factor (TNF) ␣, 11,12 which induce vascular expression of extracellular matrix proteins, particularly matrix metalloproteinases (MMPs). [13][14][15][16] Beyond their matrix remodeling properties, MMPs are involved in short-term biological processes, including regulation of vascular reactivity and leukocyte activation. [17][18][19][20][21] Interestingly, these biological processes are altered in women with preeclampsia.…”
mentioning
confidence: 99%
“…22 Stimulation of rat cardiac fibroblasts with Ang II induces the production of both NF-kB and AP-1 transcription factors and is associated with an increase in collagen I production as well as a decrease in MMP-1 expression. 23 Previous studies [24][25][26] have reported that TNF-a-induced MMP-9 expression is regulated by activation of the transcription factors NF-kB and AP-1. In our study, we found that chronic hypertension induced overexpression of AP-1 and NF-kB.…”
Section: Discussionmentioning
confidence: 99%